INTENSIFICATION OF DEEP HYDROCARBON INFLOW - Barenbaum A.A.; Zakirov S.N.; Zakirov E.S.; Indrupskii I.M.; Lukmanov A.R. (My University, 2006)
Owing to its long history, Russian and world oil and gas production has accumulated a great deal of diverse information about the specifics of fluid flow processes during oil and gas field development. Data on mature fields undergoing the final stage of exploitation are of significant interest. Several fields in Azerbaijan that have long been developed are characterized by high oil recovery factors. Evidence indicating the presence of deep hydrocarbon inflows is today being published with increasing frequency by various authors.